Penerapan Kompres Daun Kubis Untuk Kenyamanan dan Kelancaran Pengeluaran Asi Pada Ibu Postpartum - Agestina Agestina; Bunga Nuansa Putri; Nouwlia Prameswari; Dewi Anggraini (Jurnal Ilmu Kesehatan dan Gizi, 2026)
The postpartum period is a vulnerable phase often accompanied by lactation problems, particularly ineffective breastfeeding and discomfort due to breast engorgement. These conditions may reduce maternal comfort, inhibit the let-down reflex, and increase the risk of failure in exclusive breastfeeding. Therefore, safe, practical, and comprehensive non-pharmacological nursing interventions are needed. This Final Nursing Project aims to describe the implementation of cabbage leaf compresses combined with breastfeeding education to improve maternal comfort and enhance breast milk flow in postpartum mothers. This study employed a case study method using a nursing care approach involving two postpartum mothers who experienced ineffective breastfeeding and discomfort due to breast engorgement. The interventions were provided for three days and included cabbage leaf compresses and education on breastfeeding techniques. Evaluation focused on breastfeeding ability, pain level, breast condition, maternal comfort, and milk production. The results showed improvement in breastfeeding ability, indicated by the mothers’ ability to correctly demonstrate proper positioning and latch-on techniques. Infants appeared calmer during feeding, and the duration of breastfeeding increased to approximately 10 minutes per breast. Pain scores decreased from 5 to 0–3, breast tension was reduced, and maternal comfort improved. It can be concluded that the application of cabbage leaf compresses combined with breastfeeding education is effective in improving breast milk flow and maternal comfort in postpartum mothers and can be recommended as an independent nursing intervention in maternity practice.